Predictive Value of Endoscopic Observations and Biopsy After Neoadjuvant Chemoradiotherapy in Assessing the Pathologic Complete Response of Patients With Esophageal Squamous Cell Carcinoma - Taghizadeh Kermani, Ali; Ghanbarzadeh, Raha; Joudi Mashhad, Mona; Javadinia, Seyed Alireza; Emadi Torghabeh, Ali (Frontiers in Oncology, 2022)
Introduction: No standard method has been defined to evaluate the therapeutic response of esophageal cancer to neoadjuvant chemoradiotherapy (CRT). The aim of this study was to determine the predictive value of endoscopic evaluation and biopsy after CRT in predicting the complete pathologic response to neoadjuvant CRT in patients with esophageal squamous cell carcinoma (SCC). Materials and method: This prospective descriptive study was performed on patients with stage II and III esophageal SCC who could undergo esophagectomy. Patients underwent neoadjuvant CRT. 4-6 weeks after the end of treatment, re-endoscopy was performed and biopsy taken in the presence of a tumor lesion and in the absence of a tumor lesion, the marked site of the esophagus was removed as a blind biopsy. Gastrologist observations during endoscopy and the result of pathologic examination of endoscopic biopsy were recorded. The patient underwent esophagectomy. The pathology obtained from endoscopic biopsy was compared with the pathology response obtained from esophagectomy. Results: 69 patients were included in the study, of which 32 underwent esophagectomy. In endoscopic examination after CRT, 28 patients had macroscopic tumor remnants and 4 patients did not have it. Pathologic examination of the samples obtained by endoscopy showed no tumor remnant in 10 patients (31.3%) and in 22 patients (68.7%), living tumor remnants were seen in the biopsy specimen. Pathologic evaluation of the samples obtained by surgical resection showed that in 13 patients there were no viable carcinoma in the esophagus or lymph nodes removed and the rate of pathologic complete response was 40.6. Sensitivity, specificity, positive predictive value and negative predictive value of endoscopic observations were 94.7%, 23%, 64.2% and 75%, respectively. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of preoperative biopsy were 68.4%, 30.7%, 59% and 40%, respectively. Conclusion: Considering the negative and positive predictive value of endoscopic observations as well as biopsy after neoadjuvant CRT, it seems that these two methods alone are not a suitable tool for assessing the pathologic complete response after neoadjuvant treatment.